From 'Selves' to 'One Another': A Hospitable Proposal for a Post-Colonial Missions Paradigm of Interdependence. (July 2022) - Howell, Alan
The Three-Selves paradigm of establishing indigenous churches that are Self-Propagating, Self-Supporting, and Self-Governing (later including Self-Theologizing as a Fourth "Self") has been influential in shaping the "end goal" of Protestant missions. While this paradigm oriented missions towards independence, that objective was still shaped by Colonial ideals. This paper proposes a shift from the goal of independent "Selves" to an interdependent posture of "One-Another-ing" (or "Belonging") for hosts and guests. That proposal is framed by listening to the language of hospitality from the margins: a reading of oft-neglected texts (2 and 3 John) in the context of northern Mozambique, Africa.